Pattern of neoplastic and non-neoplastic lesions of ovary: a five-year study in a tertiary care centre of rural india - Maurya, Geeta; Singh, Sanjeev Kumar; Pandey, Pinki; Chaturvedi, Vineet (International Journal of Research in Medical Sciences, 2018)
Background: Most common ovarian lesions include benign non-neoplastic lesions including functional cysts and neoplastic lesions. While among cancers of female genital tract, the incidence of ovarian cancer ranks below only carcinoma of cervix and endometrium. The aim of this study was to observe and evaluate the frequency and morphological pattern of different ovarian pathologies encountered in this tertiary care centre of rural India. Methods: This was a retrospective five years observational study (2012-16) and conducted at Department of Pathology of UPUMS, Saifai. The study material included 264 histopathology specimens received in our department. Results: Total 264 cases of ovarian pathologies were studied, in which 147 cases were non-neoplastic while remaining 117 cases were neoplastic. The most common non-neoplastic lesion was follicular cyst (51.7%), followed by corpus luteal cyst (30.61%), endometriosis (15.64%). Among 117 neoplastic cases, 87 cases (74.35%) were benign, 5 cases (4.27%) were borderline tumours and 25 cases (21.36%) were diagnosed malignant. Serous cystadenoma was most common benign tumour with 53 cases (45.29%) followed by 20 cases (17.09%) of dermoid cyst and 12 cases (10.25%) of mucinous cystadenoma. While in malignant tumours, serous adenocarcinoma were most common (4.27%) followed by mucinous adenocarcinoma (2.56%). Conclusions: In our study, non-neoplastic ovarian lesions were more commonly seen than neoplastic lesions. Surface epithelial tumours were most common histologic type in all age groups. While serous adenocarcinoma was most common ovarian malignancy seen. Both non-neoplastic as well as neoplastic lesions of ovary often present with similar clinical and radiological features. So histopathological study is essential to diagnose ovarian tumours.